Spiritual and Moral Self-Awareness: The Key to Harmony and Personal Development (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Spiritual and moral self-consciousness is an important aspect of personality development based on the awareness of one's spiritual and moral nature. This article discusses the essence of spiritual and moral self-awareness, its importance for the formation of values and relationships in society, as well as ways of its development. The main emphasis is on how the development of this aspect of self-awareness contributes to spiritual growth, self-improvement, and the formation of harmonious relationships with the world around us.